2023
DOI: 10.28991/cej-2023-09-03-012
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Strength of Reinforced Concrete Beams with Brine and Olive Oil Mill Wastewater

Abstract: The authors conducted a comprehensive research study on adding olive oil mill and brine wastewater to the concrete mix to investigate torsion, bending stress, shear, and compressive strength. The total number of specimens were 33 beams 100 mm (depth) × 100 mm (width) × 500 mm (length). Three beams were used as control samples, and thirty beams were divided into two groups: fifteen samples were from an olive oil mill, and the other fifteen were brine wastewater with different percentages of additive material (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Comparing the results of this study with those of others [6][7][8][9][10] on the topic of compressive strength, we find that they are essentially identical, leading us to the conclusion that concrete to which brine wastewater has been added at a rate of up to 10% has a higher compressive strength than regular concrete.…”
Section: Strength Of Compressivesupporting
confidence: 70%
See 4 more Smart Citations
“…Comparing the results of this study with those of others [6][7][8][9][10] on the topic of compressive strength, we find that they are essentially identical, leading us to the conclusion that concrete to which brine wastewater has been added at a rate of up to 10% has a higher compressive strength than regular concrete.…”
Section: Strength Of Compressivesupporting
confidence: 70%
“…However, the observed percentage boost in compressive strength drops below that of conventional concrete by around 3% once the brine wastewater addition rate exceeds 15%. Several studies [6][7][8][9] have confirmed the accuracy of this claim. Figure 12 and Table 8 show that the compressive stress curves for concrete aged with the addition of brine wastewater follow the same general pattern as those for conventionally aged concrete.…”
Section: Strength Of Compressivementioning
confidence: 59%
See 3 more Smart Citations